Acromioclavicular Joint Injury and Repair - Baren, James P.; Rowbotham, Emma; Robinson, Philip (Seminars in Musculoskeletal Radiology, 2022)
The acromioclavicular (AC) joint is commonly injured in athletes participating in contact and overhead throwing sports. Injuries range from simple sprains to complete ligamentous disruption, and they are classified by the established Rockwood grading system. High-grade injuries are associated with fractures around the AC joint and disruption of the superior shoulder suspensory complex, a ring of osseous and ligamentous structures at the superior aspect of the shoulder. Radiographs are the mainstay of imaging of the AC joint, with magnetic resonance imaging reserved for high-grade injuries to aid classification and plan surgical management. Low-grade AC joint injuries tend to be managed conservatively, but a wide range of surgical procedures have been described for higher grade injuries and fractures around the AC joint. This review illustrates the anatomy of the AC joint and surrounding structures, the imaging features of AC joint injury, and the most commonly performed methods of reconstruction and their complications.
Keywords: acromioclavicular joint; anatomy; imaging; magnetic resonance imaging; acromioclavicular joint surgery